Type 1 Diabetes, Celiac Disease, and Neuropathy—A Nationwide Cohort Study. Issue 1 (September 2017) - Thawani, Sujata; Brannagan, Thomas H.; Lebwohl, Benjamin; Mollazadegan, Kaziwe; Green, Peter H. R.; Ludvigsson, Jonas F.
Abstract: Objective: Both type 1 diabetes (T1D) and celiac disease (CD) have been linked to an increased risk of neuropathy. This study examined the risk of neuropathy in patients with T1D compared with patients with both T1D and CD. Methods: In a nationwide population-based cohort, T1D was defined as having a diagnosis of diabetes between 1964 and 2009 recorded in the Swedish National Patient Register in individuals ⩽30 years of age. CD was defined as having villous atrophy (Marsh histopathology stage III) on small intestinal biopsy. CD cases were identified through biopsies examined between 1969 and 2008 at any of Sweden's 28 pathology departments. Nine hundred fifty-eight patients had both T1D and CD and were matched for sex, age, and calendar period with 4590 controls who only had T1D. Through Cox regression analysis, with CD as the time-dependent covariate, we estimated the risk of neuropathy in T1D patients with CD. Results: Fifty-four individuals with T1D and CD had later neuropathy (expected: n = 42). This corresponded to an adjusted hazard ratio of 1.27 (95% confidence interval = 0.95–1.71) compared with those who had T1D alone. The hazard ratio was statistically significant in the first 5 years with CD (1.67; 95% confidence interval = 1.13–2.47) but decreased to neutrality thereafter. Risk estimates were similar in men and women, and did not differ by age at CD onset. Conclusions: CD does not seem to influence the risk of neuropathy in individuals with T1D, although a small excess risk cannot be ruled out. Abstract : Supplemental Digital Content is Available in the Text.